Activation of the prostaglandin E2 EP2 receptor attenuates renal fibrosis in unilateral ureteral obstructed mice and human kidney slices. (20th May 2019) - Jensen, Michael Schou; Mutsaers, Henricus A. M.; Tingskov, Stine Julie; Christensen, Michael; Madsen, Mia Gebauer; Olinga, Peter; Kwon, Tae‐Hwan; Nørregaard, Rikke
Abstract: Aim: Renal fibrosis plays a pivotal role in the development and progression of chronic kidney disease, which affects 10% of the adult population. Previously, it has been demonstrated that the cyclooxygenase‐2 (COX‐2)/prostaglandin (PG) system influences the progression of renal injury. Here, we evaluated the impact of butaprost, a selective EP2 receptor agonist, on renal fibrosis in several models of kidney injury, including human tissue slices. Methods: We studied the anti‐fibrotic efficacy of butaprost using Madin‐Darby Canine Kidney (MDCK) cells, mice that underwent unilateral ureteral obstruction and human precision‐cut kidney slices. Fibrogenesis was evaluated on a gene and protein level by qPCR and Western blotting. Results: Butaprost (50 μM) reduced TGF‐β‐induced fibronectin (FN) expression, Smad2 phosphorylation and epithelial‐mesenchymal transition in MDCK cells. In addition, treatment with 4 mg/kg/day butaprost attenuated the development of fibrosis in mice that underwent unilateral ureteral obstruction surgery, as illustrated by a reduction in the gene and protein expression of α‐smooth muscle actin, FN and collagen 1A1. More importantly, a similar anti‐fibrotic effect of butaprost was observed in human precision‐cut kidney slices exposed to TGF‐β. The mechanism of action of butaprost appeared to be a direct effect on TGF‐β/Smad signalling, which was independent of the cAMP/PKA pathway. Conclusion: In conclusion, this study demonstrates that stimulation of the EP2 receptor effectively mitigates renal fibrogenesis in various fibrosis models. These findings warrant further research into the clinical application of butaprost, or other EP2 agonists, for the inhibition of renal fibrosis.